Attitude of Personal Information Management Among Research Scholars: A Study on University of Kerala - L R DIVYA and K G PILLAI SUDHIER (LIBRARY HERALD, 2016)
This paper aims to understand the attitude and skills of Personal Information Management (PIM) among research scholars of Faculty of Applied Sciences in the University of Kerala. PIM refers to a set of activities a person performs in order to acquire, create, store, organize, maintain, retrieve, use and distribute personal information for different purposes. The study is based on a questionnaire survey of research scholars of the six departments under the Faculty of Applied Science at University of Kerala. A structured questionnaire was designed for the data collection on the basis of objectives of the study. Questionnaire consists of both optional type questions and statements in five point Lickert scale. The study includes the full time research scholars under the Faculty of Applied Science at University of Kerala. Out of the 59 respondents, 69.60% females and 30.40% male scholars are using their lap tops for managing personal information. The study attempts to identify various factors such as age, gender and qualification of the research scholars. Majority of the respondents agreed that they know more about managing their personal information and apply it on research work and it helps to present papers. The study revealed that 49.15% research scholars agreed that PIM helps them to present papers and motivate research work. The findings of the study indicate that the respondents find difficulties in updating. Analysis also showed that most of the research scholars have above average skills on information searching and maintenance. The paper highlights the attitude of research scholars towards personal information management.